The anti-inflammatory mechanisms of Hsp70 - Borges, Thiago J.; Wieten, Lotte; van Herwijnen, Martijn J.; Broere, Femke; Van Der Zee, Ruurd; Bonorino, Cristina; Van Eden, Willem (Frontiers in Immunology, 2012)
Immune responses to heat shock proteins (Hsp) develop in virtually all inflammatory diseases; however, the significance of such responses is only now becoming clear. In experimental disease models, Hsp administration can prevent or arrest inflammatory damage, and in initial clinical trials in patients with chronic inflammatory diseases, Hsp peptides have been shown to promote the production of anti-inflammatory cytokines, indicating immunoregulatory potential of Hsp. Therefore, the presence of immune responses to Hsp in inflammatory diseases can be seen as an attempt of the immune system to correct the inflammatory condition. Hsp70 can modulate inflammatory responses in models of arthritis, colitis and graft rejection, and the mechanisms underlying this effect are now being elucidated. Incubation with microbial Hsp70 was seen to induce tolerogenic dendritic cells (DCs) and to promote a suppressive phenotype in myeloid-derived suppressor cells and monocytes. These DC could induce regulatory T cells (Tregs), independently of the antigens they presented. Some Hsp70 family members are associated with autophagy, leading to a preferential uploading of Hsp70 peptides in MHC class II molecules of stressed cells. Henceforth, conserved Hsp70 peptides may be presented in these situations and constitute targets of Tregs, contributing to downregulation of inflammation. Finally, an interfering effect in multiple intracellular inflammatory signaling pathways is also known for Hsp70. Altogether it seems attractive to use Hsp70, or its derivative peptides, for modulation of inflammation. This is a physiological immunotherapy approach, without the immediate necessity of defining disease-specific auto-antigens. In this article, we present the evidence on anti-inflammatory effects of Hsp70 and discuss the need for experiments that will be crucial for the further exploration of the immunosuppressive potential of this protein.